Detecting fake news by enhanced text representation with multi-EDU-structure awareness. (15th November 2022) - Wang, Yuhang; Wang, Li; Yang, Yanjie; Zhang, Yilin
Abstract: Since fake news poses a serious threat to society and individuals, numerous studies have been brought by considering text, propagation and user profiles. Due to the data collection problem, these methods based on propagation and user profiles are less applicable in the early stages. A good alternative method is to detect news based on text as soon as they are released, and a lot of text-based methods were proposed, which usually utilized words, sentences or paragraphs as basic units. But, word is a too fine-grained unit to express coherent information well, sentence or paragraph is too coarse to show specific information. Which granularity is better and how to utilize it to enhance text representation for fake news detection are two key problems. In this paper, we introduce Elementary Discourse Unit (EDU) whose granularity is between word and sentence, and propose a multi-EDU-structure awareness model to improve text representation for fake news detection, namely EDU4FD. For the multi-EDU-structure awareness, we build the sequence-based EDU representations and the graph-based EDU representations. The former is gotten by modeling the coherence between consecutive EDUs with TextCNN that reflect the semantic coherence. For the latter, we first extract rhetorical relations to build the EDU dependency graph, which can show the global narrative logic and help deliver the main idea truthfully. Then a Relation Graph Attention Network (RGAT) is set to get the graph-based EDU representation. Finally, the two EDU representations are incorporated as the enhanced text representation for fake news detection, using a gated recursive unit combined with a global attention mechanism. Experiments on four cross-source fake news datasets show that our model outperforms the state-of-the-art text-based methods. Our results suggest that considering EDU and its structural features could enhance the text representation for fake news detection. Highlights: Using EDU expressing content with an intermediate granularity to detect fake news. A sequence-based EDU representation is gotten by TextCNN. A graph-based EDU representation is obtained by EDU dependency graph and RGAT. Text representation is gotten by GRU with Global Attention mechanism. Extensive experiments on four cross-source datasets demonstrate the superiority.